Comparison of solid biofuels produced from olive pomace with two different conversion methods: torrefaction and hydrothermal carbonization - Y. Gultekin, Selin; Olgun, Hayati; S. Celiktas, Melih (International Journal of Engineering and Technology, 2018)
Olive pomace is a by-product of olive oil production process and has the potential to be a solid biofuel after thermal treatment. In this study, olive pomace was treated by two thermal conversion methods: hydrothermal carbonization (HTC) and torrefaction. Experiments were carried out under the temperature values of 250, 275, 300 and 350Â°C; reaction times of 10, 20 and 30 minutes for torrefaction and temperature values of 180, 200 and 220Â°C; reaction time of 2, 3 and 4 hours for HTC. Products with the same energy yield value (62 %) Â obtained the higher heating values of 23.73 and 25.20 MJ/kg for torrefaction (275Â°C for 20 minutes) and hydrothermal carbonization (220Â°C for 2 hours), respectively. Hydrothermal carbonization method has the potential to produce chars at lower temperature values and without a drying process; and obtain products with improved higher heating values, energy yields and atomic O/C and H/C ratios compare to torrefaction products.Â Â